2018
DOI: 10.1080/03091929.2018.1492720
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of solid objects in the Pencil Code using an immersed boundary method and overset grids

Abstract: Two methods for solid body representation in flow simulations available in the Pencil Code are the immersed boundary method and overset grids. These methods are quite different in terms of computational cost, flexibility and numerical accuracy. We present here an investigation of the use of the different methods with the purpose of assessing their strengths and weaknesses. At present, the overset grid method in the Pencil Code can only be used for representing cylinders in the flow. For this task it surpasses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This indicated that OGA implementation yields a similar accuracy in terms of modeling wake characteristics compared to other techniques. Aarnes et al [22] further showed that for the study of two dimensional flow over a circular cylinder using IBM implementation, the domain requires an approximately 18.1 times more grid points than that used in the Overset method to achieve a similar accuracy [22]. The cost and time required for computation would therefore increase, as was observed in another study by Tay et al [36] for flapping airfoil simulations.…”
Section: Stationary Panelmentioning
confidence: 97%
See 1 more Smart Citation
“…This indicated that OGA implementation yields a similar accuracy in terms of modeling wake characteristics compared to other techniques. Aarnes et al [22] further showed that for the study of two dimensional flow over a circular cylinder using IBM implementation, the domain requires an approximately 18.1 times more grid points than that used in the Overset method to achieve a similar accuracy [22]. The cost and time required for computation would therefore increase, as was observed in another study by Tay et al [36] for flapping airfoil simulations.…”
Section: Stationary Panelmentioning
confidence: 97%
“…Here, we provide benchmark results for the wake of finite aspect ratio stationary and pitching panels, using the overset solution technique implemented in OpenFOAM. The requirement of smaller grids in overset method, as seen in a study by Aarnes et al [22] for simulating flows over two dimensional bodies, highlighted its potentially better computational efficiency compared to other techniques, such as IBM [11,23]. We therefore utilize OGA method for simulating flows over three dimensional square panels.…”
Section: Introductionmentioning
confidence: 99%
“…• Flows around immersed solid objects (Aarnes et al, 2019(Aarnes et al, , 2020; N. E. L. Haugen & Kragset, 2010), • Test-field method for turbulent MHD transport (A. Warnecke et al, 2018), • Mean-field MHD (Jabbari et al, 2013;Kemel et al, 2013),…”
Section: High-level Functionalitymentioning
confidence: 99%
“…a cylinder in a cross flow, and the use of more complex boundary conditions. In this connection, Aarnes et al (2020) have compared two different approaches for handling solid bodies within a fluid flow. One is the immersed boundary method and the other is the overset grid method.…”
Section: Introductionmentioning
confidence: 99%